Challenges in COVID-19 Pandemic Triaging: An Indian and US Perspective - Muralidhar Varma; Robin Sudandiradas; Mauli Mahendra Patel; Trini Ann Mathew; Marcus Zervos; Shashikiran Umakanth; Asha Kamath; Mahadev Rao; Vandana Kalwaje Eshwara; Chiranjay Mukhopadhyay; Vijaya Arun Kumar (Emergency Care and Medicine)
Background/Objectives: The COVID-19 pandemic overwhelmed many health care facilities with patients, leading to an increased risk of potential transmission. Though the disease process was identical, the triaging system was unique at different sites, without a unified system for emergency department triaging globally. Proper implementation of pre-screening and triaging is of paramount importance in tertiary care settings to prevent nosocomial spread of infection. Methods: Each country has its own triage guidelines and Infection, Prevention, and Control policies developed by its health ministry and may face significant challenges in implementing them. Triage guidelines followed by two tertiary care hospitals in Detroit, United States of America and Manipal, India are compared during the early phases of the COVID-19 pandemic. Results: This paper offers a unique perspective of the challenges experienced with the hospital triage practices and provides solutions to address them. The future trajectory of COVID-19 epidemiology in both countries will be determined by the adherence to best practices in Infection Prevention and Control and triage protocols. The healthcare facility triage algorithm is constantly evolving in both settings as new evidence is being added to hospital epidemiology and infection prevention practices. Conclusions: Training healthcare workers on new triage protocols is required. It is critical for infectious disease doctors, clinical microbiologists, hospital epidemiologists, and Infection Prevention and Control (IPC) staff to collaborate with clinicians, nurses, and other ancillary staff in order to successfully implement the triage protocols. Developing and modifying guidelines for cleaning hospital triage areas and providing high throughput for patient care are also important lessons learned. Usage of face shields and the quality of Personal Protective Equipment (PPE) should be ensured for all healthcare workers (HCWs). Resilient staff and resilient hospital infrastructure are crucial for a sustainable response to future pandemics.